Prediction of the Distribution and Effect of Diameters of the Cylinder and the Piston Post-Manufacture on the Operation of Gas-Operated Automatic Rifles - Hung, Nguyen Van (Vietnam Journal of Science and Technology, 2023)
The article is focused on the application of the reliability and experimental statistics theory to predict the distribution of the cylinder inner diameter and the piston outer diameter post-manufacture for the gas-operated automatic rifles. Besides, the influence of these dimensions on the operation of the automatic system was also studied in 5 cases with the maximum, minimum, and the most probable. The study object in the article is 7.62mm AKM-1 rifles. Research results show that the cylinder inner diameter and the piston outer diameter post-manufacture of 7.62mm AKM-1 rifles follow the normal distribution. The research results of the article can be used to establishing technical conditions for new gun acceptance post-manufacture.